The Psychology of Silicon Valley Ethical Threats and Emotional Unintelligence in the Tech Industry - Cook, Katy (Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
"A welcome journey through the mind of the world's most influential industry at a time when understanding Silicon Valley's motivations, myths, and ethics are vitally important." - Scott Galloway, Professor of Marketing at NYU Stern School of Business, USA, and author of The Algebra of Happiness and The Four "The Psychology of Silicon Valley is a remarkable story of an industry's shift from idealism to narcissism and even sociopathy. But deep cracks are showing in the Valley's mantra of 'we know better than you.' Katy Cook's engaging read has a message that needs to be heard now." - Richard Freed, author of Wired Child "This book offers readers a glimpse behind the "emotional scenes" as tech companies come out psychologically firing at their consumers. Unless these practices are exposed and made public, tech companies will continue to shape our brains and not in a good way." - Larry D.Rosen, Professor Emeritus of Psychology, Author of The Distracted Mind: Ancient Brains in a High Tech World Misinformation. Job displacement. Information overload. Economic inequality. Digital addiction. The breakdown of democracy, civility, and truth itself. This open access book explores the conscious and unconscious norms, values, and characteristics that drive behaviors within the high-tech capital of the world, Silicon Valley, and the sector it represents. In an era where the reach and influence of a single industry has the potential to define the future of our world, it has become apparent just how little we know about the organizations driving these changes. The Psychology of Silicon Valley offers a revealing look inside the mind of world's most influential industry and how the identity, culture, myths, and motivations of Big Tech are harming society. The book argues that the bad values and lack of emotional intelligence borne in the vacuum of Silicon Valley will have lasting consequences on everything from social equality to the future of work to our collective mental health. Katy Cook expertly walks us through the psychological landscape of Silicon Valley, including its leadership, ethical, and cultural problems, and artfully explains why we cannot afford to ignore the psychology and values that are behind our technology any longer. Katy Cook is Founder and Director of the Centre for Technology Awareness. She is an expert on the intersection of technology, ethics, and psychology and holds a PhD and two MAs in psychology and modern culture studies.